1998
DOI: 10.1016/s0005-2736(98)00163-1
|View full text |Cite
|
Sign up to set email alerts
|

Binding of prothrombin and its fragment 1 to phospholipid membranes studied by the solvent relaxation technique

Abstract: The phospholipid headgroup mobility of small unilamellar vesicles composed of different mixtures of phosphatidyl-L-serine (PS) and phosphatidylcholine is characterized by the solvent relaxation behavior of the polarity sensitive dyes 6-propionyl-2-(dimethylamino)naphthalene (Prodan) and 6-palmitoyl-2-[trimethylammoniumethyl]-methylamino]naphthalene chloride (Patman). If the PS content exceeds 10%, the addition of calcium leads to a substantial deceleration of the solvent relaxation of both dyes, indicating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…a strong red shift to about 515 nm at high ethanol concentrations (Fig. This behaviour strongly suggests that no major changes in both polarity and viscosity of the dye environment take place, as it has been shown extensively that Patman is quite sensitive to any such change [22,23,28]. Thus, it might be assumed that again some kind of phase transition might occur similar to the DPPC bilayer system.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…a strong red shift to about 515 nm at high ethanol concentrations (Fig. This behaviour strongly suggests that no major changes in both polarity and viscosity of the dye environment take place, as it has been shown extensively that Patman is quite sensitive to any such change [22,23,28]. Thus, it might be assumed that again some kind of phase transition might occur similar to the DPPC bilayer system.…”
Section: Resultsmentioning
confidence: 88%
“…The validity of this approach has been demonstrated in several recent publications [22][23][24], and summarised in a few reviews [28,35,36] phase bilayers is very slow; thus, hardly any red shift with time is detectable (Fig. The validity of this approach has been demonstrated in several recent publications [22][23][24], and summarised in a few reviews [28,35,36] phase bilayers is very slow; thus, hardly any red shift with time is detectable (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Recent studies have demonstrated that suitable fluorescent dyes located within either the hydrophilic headgroup region or the hydrophobic core of lipid bilayers facilitate direct observation of viscosity and polarity changes at the local environments of the probes [32–35]. Here we measured the effects of membrane peptides upon the SR of the fluorescent dye 6‐hexadecanoyl‐2‐(((2‐(trimethylammonium)ethyl)methyl)amino)‐naphthalene chloride (Patman) [33,36–38], incorporated in the vicinity of the glycerol interface within the phospholipid domains in the lipid/PDA vesicles (Fig. 1).…”
mentioning
confidence: 99%